The Emancipated Student: Rethinking Knowledge, Equality and Democracy - Bakhtiar, Siavash (European Journal of Social Science Education and Research, 2021)
This paper’s ambition is to act as a short memento for novice language teachers. It is based on a reflexive practice that stems from my personal work experience as secondary school language teacher. Drawing upon Jacques Rancière’s portrayal of the paradoxical relation between explanation and emancipation, and Gaston Bachelard’s notion of epistemological obstacle, the article aims at giving way to a reflexion on the challenges of teaching a foreign language to a group of students coming from a particular cultural linguistic background in a secondary school. According to this perspective, which breaks away from common sense, the difficulties to learn of new language should not be understood in terms of lack or impairment, but rather as the presence of an a priori significant knowledge. From this alternative way to engage with education research emerges a political argument that does not envision equality between teachers and learners, and their emancipation, as a postponed goal, but instead as a presupposition to any democratic teaching practice.
Keywords: Language Teaching – Reflexive Practice – Crisis in Education – Epistemological Obstacle – Jacques Rancière – Emancipation